Patients' treatment preferences for potentially resectable tumors of the head of the pancreas. Issue 2 (February 2020) - Molinari, Michele; El-Tawil, Karim; Swaid, Forat; Fiorentini, Guido; Bou-Samra, Patrick; Sharma, Chakshu; Liu, Hao; Rahman, Sheikh Hasibur; Hurton, Scott; Tsung, Allan
Abstract: Background: The primary aim of this study was to assess if patients with potentially resectable ductal adenocarcinoma (PDAC) of the head of the pancreas would choose a Whipple procedure versus palliative chemotherapy. Methods: A cohort of adults with radiological resectable PDAC was enrolled at a tertiary Canadian teaching hospital. Participants were informed about treatment options, expected outcomes, and adverse events using data from the most recent scientific literature. Probability trade-off (PTO) was used to elicit treatment preferences. Results: Surgery was preferred by all participants except one (96.7% vs. 3.3%; P = 0.0001). For 90% of participants preferring surgery, the main reason was the hope of being cured (P = 0.001). If the risk of perioperative mortality was higher than 57%, the risk of perioperative morbidity higher than 85% and the survival benefit was less than 4 months, half of the participants preferred palliative chemotherapy. The likelihood of needing blood transfusions, the length of hospital stay, and long-term consequences such as diabetes or pancreatic exocrine insufficiency were negligible concerns to participants. Conclusions: Informed patients with early-stage PDAC prefer resection over palliative chemotherapy. The dominating factor influencing their decision is the hope of a cure that overshadow the risks of complications, mortality and recurrent disease.